How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport de l’échange de connaissances - Koomar, Saalim; Rasolohery, Hasiniavo; Oojorah, Avinash; Udhin, Waaiza (EdTech Hub, 2025)
This is a report on a knowledge exchange visit between the Ministry of National Education of Madagascar and the Mauritius Institute for Education. The visit focused on sharing lessons and discussing ongoing projects related to technology in education. Key objectives included presenting successes and challenges of distance learning, discussing pedagogical design and digital platforms, and exploring long-term collaboration. School visits provided insights into technology integration in classrooms and teacher experiences. The report details the workshop's activities, participants, and key points, emphasising the importance of data-driven projects, feedback mechanisms, and continuous evaluation. Recommendations for future collaboration include short-term actions like remote communication and training, medium-term initiatives like co-presenting at conferences and personnel exchange, and long-term goals like co-applying for regional research projects. Keywords: teacher professional development; Madagascar; Moodle; knowledge exchange; EdTech; pedagogy Ce rapport porte sur une visite d’échange de connaissances entre le Ministère de l’Éducation Nationale de Madagascar et le Mauritius Institute for Education. La visite avait pour objectif de partager les enseignements tirés et de discuter des projets en cours liés aux technologies éducatives. Les principaux objectifs comprenaient la présentation des succès et des défis de l’apprentissage à distance, la discussion sur la conception pédagogique et les plateformes numériques, ainsi que l’exploration d’une collaboration à long terme. Les visites d’écoles ont permis d’observer l’intégration des technologies en classe et l’expérience des enseignants. Le rapport détaille les activités de l’atelier, les participants et les points clés, en mettant l’accent sur l’importance des projets basés sur les données, des mécanismes de retour d’information et de l’évaluation continue. Les recommandations pour une future collaboration incluent : Actions à court terme : communication et formation à distance; Initiatives à moyen terme : co-présentation lors de conférences et échanges de personnel; Objectifs à long terme : candidature conjointe à des projets de recherche régionaux. Mots clés: formation pédagogique; Madagascar; Moodle; échange de connaissances; technologie dans l’éducation; pédagogie An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing BETA - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a report on the Beta testing of a digital learning platform and applications developed for the Ministry of Education in Madagascar. The project aims to train 16,000 teachers, with 2,000 utilising distance learning via tablets. The Beta user testing focused on the pedagogical relevance, usability, and ergonomics of the platform and two offline applications. Twenty-one teachers participated, evaluating tasks like launching applications, navigating content, accessing multimedia, and completing exercises / evaluations. Results showed significant improvement from the Alpha user testing, with high success rates for accessing and navigating modules. However, over 50% of users still found the platform difficult to use, particularly for login, navigation, and profile modification. The applications were generally functional but needed adjustments to content presentation and visual quality. Recommendations included simplifying the platform's interfaces, enhancing user guides, and addressing specific content issues. The document emphasises the importance of ongoing quality assurance and an iterative approach to refining the platform. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce rapport porte sur le test Beta d’une plateforme d’apprentissage numérique et des applications développées pour le Ministère de l’Éducation à Madagascar. Le projet vise à former 16 000 enseignants, dont 2 000 via l’apprentissage à distance sur tablette. Les tests utilisateurs en phase Beta ont évalué la pertinence pédagogique, l’ergonomie et la convivialité de la plateforme ainsi que de deux applications hors ligne. Vingt et un enseignants ont participé, réalisant des tâches telles que le lancement des applications, la navigation dans les contenus, l’accès aux éléments multimédias et la réalisation d’exercices/évaluations. Les résultats montrent une amélioration significative par rapport aux tests Alpha, avec des taux de réussite élevés pour l’accès et la navigation dans les modules. Cependant, plus de 50 % des utilisateurs ont encore rencontré des difficultés, notamment pour la connexion, la navigation et la modification du profil. Les applications étaient globalement fonctionnelles, mais nécessitaient des ajustements dans la présentation des contenus et la qualité visuelle. Les recommandations incluent la simplification des interfaces de la plateforme, l’amélioration des guides utilisateurs et la correction de problèmes spécifiques liés aux contenus. Le document souligne l’importance de l’assurance qualité continue et d’une approche itérative pour affiner la plateforme. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
Keywords: HLR3; _r:AddedByZotZen

EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)